2022
DOI: 10.1155/2022/3288308
|View full text |Cite
|
Sign up to set email alerts
|

Formal  Model and Analysis for the Random Event in the Intelligent Car with Stochastic Petri Nets and Z

Abstract: With the continuous development of science and technology, people’s lifestyle becomes more and more intelligent, especially in intelligent transportation. However, running in a random environment, safety can be affected by various factors during operation. For an intelligent car, guaranteeing its safety in operation is important to the passengers in the vehicle. So, it is vital to verify the safety of the system of the smart car. This study proposes an integration formal method with stochastic Petri nets and Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the study by Liu et al [33], the SPZN model has been proven to have good performance, as shown in Table 10. It can be seen from the case in Section 5 that after refining the established SPZN model, the number of places, transitions, and reachable marking is significantly reduced, relevant data are shown in Table 11 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Liu et al [33], the SPZN model has been proven to have good performance, as shown in Table 10. It can be seen from the case in Section 5 that after refining the established SPZN model, the number of places, transitions, and reachable marking is significantly reduced, relevant data are shown in Table 11 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The description above demonstrates that the intelligent networked vehicle system is a complex network with numerous concurrent structures and a high degree of randomness. Consequently, the paper utilizes SPZN [33], a formal modeling tool proficient in capturing concurrency and randomness.…”
Section: Intelligent Networked Vehiclesmentioning
confidence: 99%